A hierarchical model to enhance financial and strategic performance of an oil and gas company in Malaysia - Krishnan, Deven; Islam, Rafikul; Mhd. Sarif, Suhaimi (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this study intends to develop a hierarchical model through prioritisation of the core competencies with respect to competitive advantage, financial and strategic performance for an oil and gas company in Malaysia. Design/methodology/approach – Mixed method approach used in the present research. Initially, interviews were conducted to solicit information about the company’s core competencies, competitive advantage, and financial and strategic performance. The interview findings used for questionnaire development to rank core competencies with respect to competitive advantage, financial and strategic performance. The survey results were analysed using the analytic hierarchy process (AHP), a mathematical model and is synthesised using Super Decisions Software. Findings – The study developed a hierarchical model and can be set as a benchmark for prioritising core competencies, with respect to competitive advantage, financial and strategic performance for oil and gas companies. Practical implications – The prioritisation results will help the company considered in the present research and also the similar companies to optimise their resources and energy to focus on the desired and the most influential core competencies. Social implications – As the oil industry develops competitive advantage, its success will cascade down to stimulate the nation’s growth, support industry and services expansion and eventually develop the nation. Originality/value – This study is a first of its kind in using AHP to rank core competencies with respect to competitive advantage, financial and strategic performance for an oil and gas company. The results can be used by oil and gas companies to enhance their overall performance.